Pemberian Massage Tengkuk dan Massage Ototpectoralis Mayor Terhadap Pengeluaran Asi pada Ibu Menyusui - Pupun Padillah, Eneng; Kurnia Dewi, Meinasari; Anggraeni K, Milka (Public Health and Safety International Journal, 2025)
Exclusive breastfeeding is one of the world's efforts to prepare healthy successors froman early age. The World Health Organization (WHO) and the United Nation Children'sFund (UNICEF) advise every mother who gives birth to be able to provide exclusivebreastfeedingto her baby.The cause of failure to provide exclusive breastfeedingBasedon a survey in Indonesia,the lack of breast milk production produced, 38%of mothersstopped breastfeeding their babies. The aim of this case study is to provide neck massageand pectoralis major muscle massage to breastfeeding mothers in the work area of theMunjul Health Center UPT, Pandeglang Regency in 2024. The method in this case studyis to use a qualitative study, with a case study approach that is carried out directlyon2breastfeeding mothers. The breastfeeding mothers are divided into 2, namely: thefirsbreasfeeding mother is given a neck massage. And the second breastfeeding mother isgiven a pectoralis muscle massage. The instruments used in this study were informedconsent, observation sheets and breast pumps as measuring tools. after a neck massagefor 10 minutes, 35 ml of breast milk production was obtained. while on the 14th dayafter the nape massage, the results of breast milk production were 40 ml, and on the 27thday, breast milk production increased and was smooth, namely 60 ml. In the 2nd respondent, namely the breastfeeding mother, on the 14th day, breast milk production was 30ml. while on the 27th day, breast milk production was still 44 ml.